Inter-linkages between liquidity and stock returns: An empirical investigation through panel cointegration - Sadia Saeed; Arshad Hassan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
This study examines long term and short term inter-linkage between liquidity dimensions and equity returns in oil and gas sector of an emerging stock market for the time period 2009-2015.Conventional liquidity ratio and Amihud ratio are used to capture Price impact. Roll estimator is employed to quantify the effective spread and transaction cost aspect of liquidity. The depth of market is measured through volume and turnover rate. Pedroni cointegration, Granger causality and vector error correction model have been applied in panel data setting. The Pedroni cointegration analysis provides evidence about the existence of long term interaction between liquidity indicators and the equity returns. The VECM reports that liquidity influences equity returns in short run and speed of adjustment is high. Moreover, bi directional casualty is observed between liquidity and equity returns. The results suggest that local market liquidity is an important driver of expected returns. The study further implies that liquidity is vital for asset pricing. Average liquidity is priced and liquidity also predicts future returns. Moreover liquidity shocks are positively correlated with return shocks. Therefore, investors must be vigilant about liquidity trends while making investment decisions.
Keywords: 330; equity returns; price impact liquidity; market depth liquidity; transaction cost liquidity; Amihud ratio; panel co-integration; granger causality; error correction model